An investigation on the second-order nonlinear optical response of cationic bipyridine or phenanthroline iridium(iii) complexes bearing cyclometallated 2-phenylpyridines with a triphenylamine substituent. Issue 25 (12th June 2018) - Hierlinger, Claus; Cordes, David B.; Slawin, Alexandra M. Z.; Colombo, Alessia; Dragonetti, Claudia; Righetto, Stefania; Roberto, Dominique; Jacquemin, Denis; Zysman-Colman, Eli; Guerchais, Véronique
Abstract : A novel cationic Ir(iii ) complex, characterized by a large NLO response, can be incorporated into a polymeric film leading to a good second-harmonic generation. Abstract : The synthesis and characterisation of six new cationic iridium(iii ) complexes bearing either 4, 4′-di- tert -butyl-2, 2′-bipyridine (d t Bubpy) or 5-NO2 -1, 10-phenanthroline along with two cyclometallated 2-phenylpyridine derivative ligands, decorated with triphenylamine groups either meta or para to the Ir–CC^N bond or para to the Ir–NC^N bond, are reported. The second-order nonlinear optical (NLO) properties of all the compounds have been determined by the electric field induced second harmonic generation technique and show that the μβ EFISH value can be tuned by the nature of the iridium coordination sphere. The dipole moment, μ, necessary to evaluate the quadratic hyperpolarizability β EFISH, was theoretically determined. The linear optical properties of the complexes are also presented and rationalised by quantum-chemical calculations. One of the prepared iridium compounds was incorporated into a polystyrene film, affording the first example of a second-order NLO active polymeric film based on a cationic organometallic complex.